'Of the People': A brief anatomy of an archetypal nationalism. Issue 1 (April 2019) - McNamara, John
The Weberian ideal-type assists a nation in symbolising its agenda to itself and ensuring the continued maintenance of the national ideal. The heroic figure and ideal-type American, embodied by the 'Founding Fathers', was and is central to American Nationalism. Weber viewed this type of charismatic authority as unsustainable beyond the period of crisis (revolution), primarily because it is not conducive to regular economic activity. The United States however, passed from charismatic authority, relatively seamlessly, to a rational form of authority while retaining its charismatic leadership in the shape of their communal national heroic icons – the Founding Fathers. Weber's conception of Charisma is analysed here in relation to the American Revolution and the Founding Fathers and is further interrogated through Hannah Arendt's analysis of revolution and the instigation of what she referred to as a 'pathos of novelty' that predominates successful revolutions and the perpetuation of national ideals and values therein.